Republic of Estonia : Staff Report for the 1999 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This 1999 Article IV Consultation highlights that real GDP growth of Estonia slowed to 4 percent in 1998. Tighter macroeconomic policies, the decline in the stock market, and banking difficulties in the wake of the Russian crisis in August 1998 dampened domestic consumption and investment. Output growth in early 1999 has remained weak. Overall, the direct impact of the Russian crisis on growth was relatively modest, mainly because Estonia had reoriented most of its trade to the West and the exposure of Estonian banks to Russian financial markets was limited.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet